Adaptive health management information systems : concepts, cases, and practical applications - Tan, Joseph K. H.; Olla, Phillip; Tan, Joshia (2021)
"Adaptive Health Management Information Systems, Fourth Edition, is a multidisciplinary text intended for healthcare students, practitioners, and researchers who want to keep pace with developments and advances in the connected health trend encompassing the field of Health Informatics & Telematics (HIT)"--
Includes bibliographical references and index.
Keywords: Information storage and retrieval systems; Management information systems